Evolving under small disruption - Dassow, Jürgen; Martín Reyes, Gema María; Vico-Vela, Francisco José (My University, 2013)
We extend the edit operators of substitution, deletion, and insertion of a symbol over a word by introducing two new operators (partial copy and partial elimination) inspired by biological gene duplication. We de ne a disruption measure for an operator over a word and prove that whereas the traditional edit operators are disruptive, partial copy and partial elimination are non-disruptive. Moreover, we show that the application of only edit operators does not generate (with low disruption) all the words over a binary alphabet, but this can indeed be done by combining partial copy and partial elimination with the substitution operator.
Keywords: Computación evolutiva; Edit operator; Evolutionary dynamics